Severe gastrointestinal bleeding from gastrojejunal neophole ulcer: fibroscopic preoperative diagnosis - Perrone, Luis; Paperán (h), Juan A; Estrugo, Roberto; Sojo, Enrique (Cirugía del Uruguay, 1975)
Special stress is placed on pre-operative fiberoptic endoscopic study in referring to a case of postgastrectomy stomal ulcer, complicated by severe gastrointestinal . bleeding. This made it possible to apply surgery with a clear diagnosis of the cause of the hemorrhage, which would not have been possible using the conventional X-Ray methods. The treatment consisted in regastrectomy, which is particularly recommended in these cases, instead of other possible therapeutic measures which are briefly described .